COVID 19:assessment of crisis management in China and the United States - Lee, Pei May; Mao, Dun (2021)
The article is an exploratory study to understand the United States and Chinese governments’ response, with different governance models, to the COVID-19 pandemic. This article looks at initial responses during the crisis, how important resources were managed, and the interplay between government and civil society during the containment phase. It employs qualitative methods by drawing on primary and secondary data. The findings reveal that a top-down government structure, as exemplified by China, has provided greater leeway to respond to the crisis